2015
DOI: 10.1111/bjep.12073
|View full text |Cite
|
Sign up to set email alerts
|

Perception of students’ intelligence malleability and potential for future success: Unfavourable beliefs towards girls

Abstract: Secondary school students seem to be knowledgeable about a gender stereotype regarding intelligence and potential for academic success which is unfavourable for female students. Implications for students' academic trajectories are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(25 citation statements)
references
References 48 publications
2
22
0
1
Order By: Relevance
“…When the general literature was examined, it was found that whilst gender is not a reliable predictor of mindset, men can adopt incremental growth mindsets more than women (Verniers & Martinot, 2015). In terms of the grade level variable, a significant difference was found in favour of 9th Grade between 9th and 5th Grade only in the incremental dimension in children.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…When the general literature was examined, it was found that whilst gender is not a reliable predictor of mindset, men can adopt incremental growth mindsets more than women (Verniers & Martinot, 2015). In terms of the grade level variable, a significant difference was found in favour of 9th Grade between 9th and 5th Grade only in the incremental dimension in children.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…There was not a statistically significant difference between males and females for the Turkish students. When the general literature was examined, it was found that gender is not a reliable predictor of mindset [23] With regard to the semi-structured interviews, when the students' answers about perceptions of intelligence are analyzed, it was found that the codes which emerged had parallels in the existing literature [1]; [4] [6]; [24]. One of the most interesting findings is that students (4 Turkish students) stated that being able to understand maths is an indicator of intelligence.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, this does not imply that the latter think that everyone has the same potential: what they think is that each individual can develop his intellectual capacity to the maximum of his own potential (Hong, Chiu, Dweck, Lin, & Wan, 1999;Inglés et al, 2015). Correlational and experimental studies have shown that these mindsets (fixed and growth) encourage students to think, feel, and behave differently (Rattan, Good, & Dweck, 2012;Verniers & Martinot, 2015). Dweck and Leggett (1988) observed that thinking about intelligence in one way or another is related to motivation and self-regulation.…”
Section: Mindsets Frameworkmentioning
confidence: 99%